Students’ Study Routines, Learning Preferences and Self-regulation: Are They Related? - Payan-Carreira, Rita; Cruz, Gonçalo (Springer, Cham, 2019)
Good self-regulatory skills and study habits seem to be essential conditions to students’ engagement with active learning approaches, critical thinking development and academic achievement. This exploratory research study aimed to assess possible relationships between students’ self-regulation, learning preferences and study routines towards their engagement in student-centered approaches. Seventy-nine undergraduate students from an integrated master program in Veterinary Medicine were surveyed at the beginning of a redesigned course. The Tangney’ short form of Self-Control Scale was used to measure students’ self-regulation, and a questionnaire with close and open-ended questions was applied to assess students’ study routines and learning preferences. The results revealed some associations between gender and self-regulation, and between self-regulation, study routines and learning preferences for the type class format. Female students presented higher self-regulation scores than male ones. Students with regular self-study habits also had higher self-regulation scores. Further research will analyze the relationship between students’ self-regulation, academic performance and critical thinking development, as well as the impact of active learning approaches in students’ study routines or learning preferences.
Keywords: Self-regulation; Study routines; Learning preferences; Active learning; Critical thinking